2016
DOI: 10.1021/acsami.6b06005
|View full text |Cite
|
Sign up to set email alerts
|

Multitask Imidazolium Salt Additives for Innovative Poly(l-lactide) Biomaterials: Morphology Control, Candida spp. Biofilm Inhibition, Human Mesenchymal Stem Cell Biocompatibility, and Skin Tolerance

Abstract: Candida species have great ability to colonize and form biofilms on medical devices, causing infections in human hosts. In this study, poly(l-lactide) films with different imidazolium salt (1-n-hexadecyl-3-methylimidazolium chloride (C16MImCl) and 1-n-hexadecyl-3-methylimidazolium methanesulfonate (C16MImMeS)) contents were prepared, using the solvent casting process. Poly(l-lactide)-imidazolium salt films were obtained with different surface morphologies (spherical and directional), and the presence of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Cytotoxicity data for 1-dodecyl-3-methylimidazolium iodide is not available, although it can be predicted to possess the toxicity between -decyl and -hexadecyl alkyl group containing imidazolium ionic liquids. The concentrations of 1-hexaydecyl-3-methylimidazolium chloride at 0.84 µg ml −1 and 1.69 µg ml −1 for antifungal and antibiofilm (for complete biofilm prevention) activities, respectively, are below the reported toxicity value of 10 µg ml −1 on fibroblast cells (Schrekker et al, 2016) and seems to be safe. Nevertheless, additional biocompatibility studies of antifungal ionic liquids are warranted for considering these compounds in prospective formulations.…”
Section: Clinical Relevancementioning
confidence: 76%
See 2 more Smart Citations
“…Cytotoxicity data for 1-dodecyl-3-methylimidazolium iodide is not available, although it can be predicted to possess the toxicity between -decyl and -hexadecyl alkyl group containing imidazolium ionic liquids. The concentrations of 1-hexaydecyl-3-methylimidazolium chloride at 0.84 µg ml −1 and 1.69 µg ml −1 for antifungal and antibiofilm (for complete biofilm prevention) activities, respectively, are below the reported toxicity value of 10 µg ml −1 on fibroblast cells (Schrekker et al, 2016) and seems to be safe. Nevertheless, additional biocompatibility studies of antifungal ionic liquids are warranted for considering these compounds in prospective formulations.…”
Section: Clinical Relevancementioning
confidence: 76%
“…The results of in vitro assays are useful for guiding treatment choices (Beardsley et al, 2018) and complementation with in vivo studies is necessary for considering potential clinical applications. Schrekker et al (2016) evaluated the biocompatibility of imidazolium ionic liquids in vitro using L929 fibroblast cells of mice. These tests revealed that cytotoxicity increases with an increase in alkyl chain length from -butyl to -decyl andhexadecyl group.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…AQACs have been shown to disrupt mature Candida biofilms by interacting electrostatically with the negatively charged biofilm surface (Jung et al, 2020). Coatings with other polymers including imidazolium salt (IS) conjugated poly(L-lactide) (PLA) have also been used to effectively prevent Candida attachment on coated surfaces (Schrekker et al, 2016).…”
Section: Preventing Candida Biofilms Using Polymer-only Coatingsmentioning
confidence: 99%
“…They are derivatives of the imidazolium cation and an inorganic or organic anion (Riduan and Zhang ). In medicine and human health, imidazolium salts have been tested for a wide range of applications, such as antifungal (Schrekker et al ), fungal antibiofilm (Raucci et al ), antibacterial (Czekański et al ; Doria et al ), antiparasitic (Martins et al ) and larvicidal (Goellner et al ) agents. With regard to the potential use of imidazolium salts in agriculture, so far, only the results of a single study have been reported.…”
Section: Introductionmentioning
confidence: 99%